Design and Validation of a Generalized Multilevel Inverter with Simplified Switching Technique. Issue 1 (20th January 2020) - Hossain, Md Liton; Abu-Siada, Ahmed; Muyeen, S M; Ibrahim, Zulkifilie; Blaabjerg, Frede
Abstract—: This paper proposes a generalized 3-phase cascaded multilevel inverter (CMLI) along with a simplified space vector pulse width modulation (SVPWM) based on 2-level inverter (2LI) topology. While conventional cascaded H-bridge inverters (CHBIs) call for a number of DC sources which increase the cost and complexity of their implementation, the proposed CMLI requires one DC source only. On the other hand, the complexity of SVPWM lies in the switching diagram that consists of a large number of triangles comprising uneven numbers of switching vectors. The generalized 3-phase CMLI proposed in this paper is aimed at reducing the number of switching vectors of each triangle. The hypothesis of the proposed CMLI-SVPWM is firstly illustrated through extensive simulation analysis using MATLAB/SIMULINK software. Feasibility of the proposed inverter is then validated through experimental measurements on a hardware prototype. Results reveal the superiority of the proposed inverter over existing ones in terms of the quality of the output voltage and current waveforms and the overall efficiency.